Toxaphene Kills Insect Pests - Hercules Incorporated (1952 Hercules Advertisements, 1952)
Advertisement for toxaphene with a photograph of a dead boll weevil and an extended list of harmful insects that can be controlled through the use of toxaphene. Originally trademarked by the Hercules Powder Company, Toxaphene was a synthetic organic insecticide toxicant primarily used in agricultural insecticides. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Toxaphene; Chemical industry; Hercules Incorporated; Corporations; Naval stores; Insecticides; Advertising, Industrial